2017
DOI: 10.1155/2017/5239487
|View full text |Cite
|
Sign up to set email alerts
|

Development of Single-Walled Carbon Nanotube-Based Biosensor for the Detection of Staphylococcus aureus

Abstract: The goal of this research is to develop a single-walled carbon nanotube-(SWCNT-) based biosensor to detect Staphylococcus aureus. The specificity of 11 bacteria and polyclonal anti-Staphylococcus aureus antibodies (pAbs) was determined using an indirect ELISA. The pAbs were immobilized onto sensor platform after the hybridization of 1-pyrenebutanoic acid succinimidyl ester (PBASE). The resistance difference (Δ ) was calculated using a potentiostat. The bacteria detected by the biosensor were observed using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Aside from DNA-detection, CNT-based sensing systems have been also actively studied towards other possible biomedical applications, including but not limited to, detection of glucose [56], pesticides [57], cholesterol [58], reactive oxygen species [59], lactate [60], cancer [61], tuberculosis [55], nucleic acids [62], malaria [63], Staphylococcus aureus [64], and anticancer drugs [65].…”
Section: Carbon Nanotubes and Bio-sensing Technologymentioning
confidence: 99%
“…Aside from DNA-detection, CNT-based sensing systems have been also actively studied towards other possible biomedical applications, including but not limited to, detection of glucose [56], pesticides [57], cholesterol [58], reactive oxygen species [59], lactate [60], cancer [61], tuberculosis [55], nucleic acids [62], malaria [63], Staphylococcus aureus [64], and anticancer drugs [65].…”
Section: Carbon Nanotubes and Bio-sensing Technologymentioning
confidence: 99%
“…CNT can be visualized as a graphite layer rolled into cylinder of a few nanometers diameter. Compared to other nanomaterials, CNTs possess a unique combi-nation of optical (near infrared luminescence), electrical (high mobility, high conductivity, higher electron transfer kinetics) and chemical (extremely high surface area 1300 m 2 /g, ability to be functionalized) properties which make CNTs suitable for various biomedical applications [90,91], A recent study investigated the binding specificity of Staphylococcus aureus by CNTs hybridized with 1-pyrenebutanoic acid succinimidyl ester (PBASE) where a moderate LOD of 4 log CFU/mL was achieved [92]. Immobilization of biomolecules on the surface of CNTs sometimes requires chemical modification, which may interfere with the electrical properties of CNTs [92,93].…”
Section: Carbon Nanotube-based Aptasensormentioning
confidence: 99%
“…In their SWCNT-biosensor developed for the detection of Staphylococcus aureus, Choi et al (2017) found that the optimum concentration of assembled SWCNTs was 0.1mg/mL to reduce the contact resistance with the gold electrodes fabricated on a silicon wafer [88]. Yet the resistance reported was in the excess of kilo-ohms.…”
Section: A Lowering Techniques Of Contact Resistancementioning
confidence: 99%
“…High resistance has the effect of limiting the on-current, and hence resulting in reduced device performance in terms of limit of detection and sensitivity as aforementioned. This contact resistance may range from kiloohms to the excess of mega-ohms [14], [31], [73], [86], [88].…”
Section: A Lowering Techniques Of Contact Resistancementioning
confidence: 99%